Redesign of Computer-Based Test (CBT) With Total Ergonomic Approach to Reduces an Academic Stress and Improve The CBT Participants Score - Dr, Iing; Adiatmika, I Putu Gede; Adiputra, Nyoman; Tirtayasa, Ketut (Journal of A Sustainable Global South; Vol 5 No 2 (2021): August 2021DO - 10.24843/jsgs.2021.v05.i02.p02, 2021)
Computer-based Test (CBT) is a form of assessment method using a set of Multiple Choice Questions (MCQs). CBT has been applied by many educational institutions to evaluate their student’s competencies, one of those institutions is medical school. The standard of the CBT examination in medical school is arranged according to the Indonesia Medical Licensing Examination which listed that the examination must be contained of 200 MCQs in 200 minutes without a break session. This standard causes academic stress on the CBT participants and able to affect the CBT score. Aims: demonstrated the total ergonomic approach CBT redesign in reducing academic stress and improving participant’s CBT score compare with the Indonesia Medical Licensing Examination CBT design. Method: this was an experimental study employed a two-period cross-over design. The study variable was the academic stress measured by the salivary cortisol level and participant’s CBT score. Result: the salivary cortisol level in the middle of CBT was decrease significantly (p<0.05) as much as 9.88 (38.98%) from the initial salivary cortisol level of 25.34 ng/mL on the Indonesia Medical Licensing Examination CBT design becoming 15.46 ng/mL on the total ergonomic approach CBT redesign. The CBT score also increase significantly as much as 5.23 points (p<0.05) or increasing 16.20% from the 32.28 points on the Indonesia Medical Licensing Examination CBT design which become 37.51 points on the total ergonomic approach CBT redesign. Conclusion: the total ergonomic approach CBT redesign was able to reduce 38.98% of the academic stress and improving 16.20% participant’s CBT score compare with the Indonesia Medical Licensing Examination CBT design. Index Terms — ergonomic, Computer-based Test (CBT), academic stress